Chiral Hydroxy Metabolite of Mebendazole: Analytical and Semi-Preparative High-Performance Liquid Chromatography Resolution and Chiroptical Properties - Paolo Guglielmi; Gaia Pulitelli; Francesca Arrighi; Daniela Secci; Marco Pierini; Roberto Cirilli (MDPI AG, 2024)
Mebendazole (MBZ) is a benzimidazole carbamate anthelmintic used worldwide for the treatment and prevention of parasitic disorders in animals and humans. A large number of in vivo and in vitro studies have demonstrated that MBZ also has anticancer activity in multiple types of cancers. After oral administration, the phenylketone moiety of MBZ is rapidly reduced to the hydroxyl group to form the chiral hydroxy metabolite (MBZ-OH). To the best of our knowledge, there is no information in the literature on the stereochemical course of transformation and the anthelmintic and antitumor activity of individual enantiomers of MBZ-OH. In the present study, we describe in detail the direct HPLC resolution of MBZ-OH on a 100 mm × 4.6 mm Chirapak IG-3 column packed with 3 μm silica particles containing amylose (3-chloro-5-methylphenylcarbamate) as a selector. At 25 °C and using pure methanol as the mobile phase, the enantioseparation and resolution factors were 2.38 and 6.13, respectively. These conditions were scaled up at a semi-preparative scale using a 250 mm × 10 mm Chiralpak IG column to isolate multi-milligram amounts of both enantiomeric forms of the chiral metabolite. The chiroptical properties of the collected enantiomers were determined and, through a theoretical study, were related to the more stable conformations of MBZ-OH. The first and second eluted enantiomers were dextrorotatory and levorotatory, respectively, in dimethylformamide solution. Finally, by recording the retention factors of the enantiomers as the water content in the water-acetonitrile mobile phases was progressively varied, U-shaped retention maps were generated, indicating a dual and competitive hydrophilic interaction liquid chromatography and reversed-phase liquid chromatography retention mechanism on the Chirapak IG-3 chiral stationary phase.